Literasi Digital Marketing Pada Start Up untuk Mahasiswa dan Calon Mahasiswa di Malaysia - Mahmud Mahmud; Sih Darmi Astuti; Usman Usman; Maulana Rafli Azami; Muhammad Iqbal Fikry Alamsyah; Astri Kurnia Lestari (BADAN PENERBIT STIEPARI PRESS, 2025)
This community service program aims to improve digital marketing literacy for students and prospective students in Malaysia, emphasizing the role of social media in start-up marketing strategies in the era of industry 4.0. Using discussion and socialization methods followed by training and mentoring programs in Kuala Lumpur involving 50 participants aged 17–25 years, with materials covering the basics of digital marketing, the use of platforms such as Instagram and Google Ads, and marketing analytics. The results showed an increase in literacy from an average score of 2.5 to 4.2 (Likert scale 1–5), especially in digital analytics (75%) and social media management (68%). As many as 80% of participants succeeded in designing digital campaigns, increasing social media engagement by 30%, and 65% planned to launch a start-up within a year. The program sparked social change, including the formation of a digital entrepreneur community in line with the Malaysia Digital Economy Blueprint. Challenges such as limited advertising budgets were overcome with free tools such as Canva. Recommendations include integrating digital marketing modules into university curricula and cross-sector collaboration for sustainability, enriching digital literacy literature in developing countries